2020
DOI: 10.1371/journal.pone.0227136
|View full text |Cite
|
Sign up to set email alerts
|

Catchment-scale export of antibiotic resistance genes and bacteria from an agricultural watershed in central Iowa

Abstract: Antibiotics are administered to livestock in animal feeding operations (AFOs) for the control, prevention, and treatment of disease. Manure from antibiotic treated livestock contains unmetabolized antibiotics that provide selective pressure on bacteria, facilitating the expression of anti-microbial resistance (AMR). Manure application on row crops is an agronomic practice used by growers to meet crop nutrient needs; however, it can be a source of AMR to the soil and water environment. This study in central Iow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Tetracycline has been widely used in livestock production, and tet ARGs are often found in the water impacted by agricultural runoff. ,, Therefore, monitoring the tetracycline-resistance gene tetO as an indicator of ARG in this study reflected the abundance of ARGs from agricultural monitoring sites. Sources of fecal contamination from agricultural activities were identified using MST markers ( CowM2 for cows and Ovmito for sheep) at sites 7, 12, and 14.…”
Section: Discussionmentioning
confidence: 99%
“…Tetracycline has been widely used in livestock production, and tet ARGs are often found in the water impacted by agricultural runoff. ,, Therefore, monitoring the tetracycline-resistance gene tetO as an indicator of ARG in this study reflected the abundance of ARGs from agricultural monitoring sites. Sources of fecal contamination from agricultural activities were identified using MST markers ( CowM2 for cows and Ovmito for sheep) at sites 7, 12, and 14.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that AMR indicators are enriched after manure application into soils reveals a risk for its further transport into waterways; an example is the occurrence of ARB and ARGs in waters with proximity to swine (Sapkota et al., 2007; Baquero et al., 2008; Garder et al., 2014; Luby et al., 2016). In an agriculturally dominated watershed in Iowa, ARG concentrations were observed to be correlated with manure application timing (Neher et al., 2020b) and indicated catchment‐scale export of ARGs and tetracycline‐ and tylosin‐resistant bacteria from agricultural sources (Rieke et al., 2018; Neher et al., 2020a). Duff et al.…”
Section: Transport Of Amr Indicators Into Soil and Watermentioning
confidence: 99%
“…Importantly, resistance rates can vary across a country or even within the same state, as reported by the CDC nationally and locally in Wisconsin 6 – 8 . Globally, differences in antibiotic susceptibility can be observed and linked with local antibiotic use in healthcare and agriculture 9 – 11 . Our prior research identified geospatial patterns across Wisconsin when analyzing AMR data at the health system level 12 .…”
Section: Introductionmentioning
confidence: 99%